Pendidikan Sosial dalam Al-Quran: Studi Literatur - Jarkasih Harahap, Ibnu Alwi; Asnil Aidah Ritonga; Mohammad Al Farabi (VISA: Journal of Vision and Ideas, 2024)
"Social education stands as a crucial element in shaping the character of individuals who exhibit responsibility and concern for society. This article delves into the role and potential of the Quran in the realm of social education. Serving as a fount of Islamic religious teachings, the Quran encapsulates profound social and ethical values. This research endeavors to pinpoint the social values embedded in the Quran and explores methods to seamlessly integrate Quranic teachings into the fabric of social education. The findings underscore that the Quran can serve as a robust compass in cultivating social awareness, empathy, compassion, and positive ethics among the younger generation. By comprehending and applying the Quranic teachings within a social context, social education emerges as a potent conduit for molding character grounded in universal values. The practical implication The essence of this research can be found in the formulation of a social education learning model centered around the Quran, a tool that educational institutions can leverage to enhance the efficacy of character education. In conclusion, the Quran emerges as a precious fount of inspiration in social education, contributing to the development of a younger generation that embodies responsibility and ethical citizenship in society.